Quantifying the influence of topographic amplification on the landslides triggered by the 2015 Gorkha earthquake - Ashok Dahal; Hakan Tanyas; P. Martin Mai; Mark van der Meijde; Cees van Westen; Luigi Lombardo (Communications Earth & Environment, 2024)
Abstract Topographic amplification is caused by the interaction between seismic waves and rough terrains. It increases shaking levels on hilltops and could lead stable slopes to the brink of failure. However, its contribution to coseismic landslide occurrence is yet to be quantified over landscapes shaken by strong earthquakes. Here, we examine how topographic amplification controls the spatial distribution of landslides triggered by the 2015 Gorkha earthquake. We find that 6–17% of coseismic failures initiate due to topographic amplification. Among these, only 13% occurred in the vicinity of the rupture zone (<40 km), presumably because proximal slopes fail due to the strong motion, irrespective of topographic amplification. Conversely, the majority of landslides (~60%) due to topographic amplification occur away from the epicentre. Our findings imply that the contribution of topographic amplification is generally overestimated in the case of strong earthquakes, an interpretation that rather holds only far from the rupture zone.